Metaphorical Interpretation of Genesis in M. M. Prishvin’s Works - Chumakov, Aleksey; Shnurenko, Tatiana; Zhilyakov, Sergey; Mochalin, Anatoly (Journal of History Culture and Art Research, 2018)
This article explores the originality of M.M. Prishvin’s metaphor in his own works. The main directions of metaphorization, forming the figurative and semantic basis of the artistic method and the philosophy of the writer, are considered. The role of metaphor in creation of the author’s image of the world, representing the dialectical tropocentric system of relations between form and content, refracted in various aspects of the existence of the text is defined. It is shown that a metaphorical understanding of being forms the author’s image of the world, on the one hand, and realistic and even naturalistic, on the other hand, having a powerful mythological overtones and deep philosophical content. The main method by which the outstanding Russian writer of the first half of the XX century solves epistemological, ethical, aesthetic, and ideological tasks in the prose texts of various genres, is a metaphor. Analysis of the prose of M.M. Prishvin allows us to assert that in the work of the writer metaphor forms the semantic core of the author's rhetoric and characteristics, composition and system of images. In the works of M.M. Prishvin, both large and small forms of metaphor, form a unified system that interacts with all elements of the text and represents the figurative and semantic framework of the author's thoughts. The individual-author's metaphor becomes for the writer a universal tool of knowledge, thanks to which an aesthetic synthesis of various spheres of being is carried out: natively-natural, social-human, spiritual-metaphysical.